Real world patterns of care in HER2-overexpressing breast cancer: Results of a survey of TEACH clinical trial investigators in 2011. (February 2017) - Chavarri-Guerra, Y.; St. Louis, J.; Bukowski, A.; Soto-Perez-de-Celis, E.; Liedke, P.E.R.; Symecko, H.; Moy, B.; Higgins, M.; Finkelstein, D.M.; Goss, P.E.
Abstract: Background: HER2-overexpressing breast cancer (BC) is common among young patients and poses a public health burden. Adjuvant anti-HER2/neu therapy with trastuzumab reduces the risk of recurrence and improves survival. Methods: A web-based survey was sent to 386 physicians of the "TEACH" trial in 2011 to determine access to HER2/neu testing and treatment patterns for HER2-overexpressing BC. Results: There were 151 responders (39%) from 28 countries. Ninety-seven percent reported HER2/neu expression is routinely measured in their institutions by immunohistochemistry (85%), FISH (80%) and other methods (16%). Twenty percent of responders from Asia reported that the test was not routinely available. Forty-eight percent of participants reported instances when adjuvant HER2-directed therapy was recommended to a patient who eventually did not receive it. Reasons for not receiving trastuzumab was cost (73%, p < 0.0001) in low- and middle-income countries and co-morbidities in high-income countries (43%, p = 0.003). Conclusions: This survey reflects the availability of HER2/neu testing and anti-HER2/neu therapy among physicians who participated in TEACH. A high proportion of women with HER2-overexpressing BC may not receive standard adjuvant therapy due to unavailability of the test and cost of therapy. Despite having some limitations, such as a possible selection bias of participating physicians, variable definitions of access to healthcare among respondents, and changes in trastuzumab availability since 2011, our results demonstrate that access to care and region of practice impact the implementation of cancer treatments. Highlights: HER2+ breast cancer patients in LMICs may not receive standard adjuvant therapy. Responders reported instances when they recommended trastuzumab but the patient did not receive it. Our survey cites cost and lack of high quality HER2 testing as barriers to adjuvant therapy.